Nonclassical Hydrophobic Effect in Micellization: Molecular Arrangement of Non‐Amphiphilic Structures. Issue 1 (15th December 2017) - Uchman, Mariusz; Abrikosov, Alexei I.; Lepšík, Martin; Lund, Mikael; Matějíček, Pavel
Abstract: Micellization brought about by nonclassical hydrophobic effect invokes enthalpy as the driving force. Thus, the underlying molecular phenomena differ from the entropically dominated hydrophobic effect. In quest for a molecular‐scale understanding, we report on the molecular arrangement of nonamphiphilic structures of an anionic boron cluster compound, COSAN. We synergistically combine experimental (NMR and calorimetry) and theoretical (molecular dynamics and quantum chemical calculations) approaches. The experimental data support the mechanism of closed association of COSAN, where the self‐assembly is driven by the enthalpy contribution to the free energy. Molecular dynamics simulations in explicit solvent show that water molecules form a patchy network around COSAN molecules, giving rise to the strong hydrophobic self‐association. In the second solvation shell, water forms a slightly hydrophilic "spot" close to the C‐H segments of the cluster. The simulations further show a counterintuitive short‐range [COSAN] − ∙∙∙[COSAN] − attraction and Na + ∙∙∙[COSAN] − repulsion. Quantum chemical calculations reveal a major role of solvation in stabilizing the contact pairs. Further, the calculations show the parallel/X‐shape geometrical arrangements of COSAN dimers as the most preferred. Lastly, dihydrogen bonding are found to influence the structure of micelles. In summary, we provide a molecular view of nonclassical micellization that can be extended to other amphiphiles like boranes. Abstract : Anionic boron cluster compound COSAN is an amphiphilic molecule that self‐assembles in water. Despite its amphiphilic behavior, COSAN has a nonamphiphilic structure. The driving force of the aggregation of such molecules is nonclassical hydrophobic effect. The molecular mechanism of self‐assembly is revealed by a combination of NMR and calorimetry with theoretical methods of molecular dynamics and quantum chemical calculations.